2014
DOI: 10.1007/s12034-014-0725-7
|View full text |Cite
|
Sign up to set email alerts
|

Optical, mechanical and TEM assessment of titania-doped Bi2V1−x Ti x O5⋅5−δ bismuth vanadate oxides

Abstract: Optical, mechanical and structural behaviors have been studied for titania-doped Bi 2 V 1−x Ti x O 5•5−δ which are used as electrolytes for intermediate temperature fuel cells. Parameters like band gap (E g), Urbach energy (E u), refractive index, hardness (H) and fracture strength (K) have been calculated as a function of dopant concentration, i.e. 0•05 ≤ x ≤ 0•2. Furthermore, analysis of transmission electron microscopy (TEM) images for all the oxides was conducted along with line spectra of planes. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The exponent n is an index whose value characterizes the optical absorption process. n = 1/2 and n = 2 denote direct allowed and indirect allowed transitions, respectively, while n = 3/2 and n = 3 are for direct forbidden and indirect forbidden transitions, respectively [37]. Further, the obtained diffuse reflectance spectra have been converted into Kubelka-Munk function by introducing the quantity F(R∞) (proportional to α).…”
Section: Uv-vismentioning
confidence: 99%
See 1 more Smart Citation
“…The exponent n is an index whose value characterizes the optical absorption process. n = 1/2 and n = 2 denote direct allowed and indirect allowed transitions, respectively, while n = 3/2 and n = 3 are for direct forbidden and indirect forbidden transitions, respectively [37]. Further, the obtained diffuse reflectance spectra have been converted into Kubelka-Munk function by introducing the quantity F(R∞) (proportional to α).…”
Section: Uv-vismentioning
confidence: 99%
“…It has been observed that doping of Al and Ti at V-site results in the blue shift of direct band gap of all the doped samples. Kaur et al [37] have studied the Ti III -doped BIVOX system and have correlated the smaller band gap of the material with the higher conductivity due to optimization of the oxygen vacancies concentration located on equatorial lines of the perovskite layers (VO 3.5 ) 2− . Similarly, in the present system, the observed lowest value of E g for the composition x = 0.175 (even compared to parent compound) can be correlated to the presence of comparatively higher order of oxide ion vacancies than other prepared compositions.…”
Section: Uv-vismentioning
confidence: 99%